2015
DOI: 10.11606/issn.2178-2075.v6i2p66-83
|View full text |Cite
|
Sign up to set email alerts
|

Design thinking como ferramenta para geração de inovação: um estudo de caso da Biblioteca Universitária da UDESC

Abstract: <p class="corpodotexto">Este estudo aborda o uso do <em>design thinking</em> como ferramenta de interação e aproximação entre os colaboradores, comunidade e usuários da Biblioteca da Universidade do Estado de Santa Catarina (BU/UDESC). Essa nova abordagem de inovação, voltada para o <em>design thinking</em>, possibilita agregar valor às propostas a serem implantadas, pois são pensadas e estruturadas de forma participativa. O objetivo do estudo é utilizar as técnicas do <em>d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
2
0
6
Order By: Relevance
“…In Brazil, Ramírez and Zaninelli (2017) reported success cases of the DT methodology and its importance for information science. DT as a methodology for achieving innovation in a library was also reported by Juliani et al (2015). The objective of the application of the DT in the library at University of Santa Catarina was to generate innovative services in that space.…”
Section: Considerationsmentioning
confidence: 97%
See 1 more Smart Citation
“…In Brazil, Ramírez and Zaninelli (2017) reported success cases of the DT methodology and its importance for information science. DT as a methodology for achieving innovation in a library was also reported by Juliani et al (2015). The objective of the application of the DT in the library at University of Santa Catarina was to generate innovative services in that space.…”
Section: Considerationsmentioning
confidence: 97%
“…The objective of the application of the DT in the library at University of Santa Catarina was to generate innovative services in that space. The study concluded that the approach allowed the delivery of quality information and promoted the informational accessibility of the university library (Juliani et al , 2015).…”
Section: Considerationsmentioning
confidence: 99%
“…Según Juliani et al, (2015) resulta destacable la diversidad de modalidades en las que el design thinking es interpretado e implementado. No obstante, existe una coincidencia en señalar 5 etapas de desarrollo de la metodología (Figura 2): la observación y empatía, definir ideas, visualizar ideas, experimentar con prototipos, y probar, evaluar y retroalimentar soluciones desde los procesos de razonamiento abductivo para marcar un antes y un después en el área de conocimiento con la que entra en contacto.…”
Section: Design Thinking Como Metodología De Aprendizajeunclassified
“…El CRAI en la actualidad debe centrar sus esfuerzos y recursos para afrontar los retos de un mundo en transformación constante; donde la información, el conocimiento y el proceso de aprendizaje tienen valor estratégico para el desempeño profesional exitoso. Así, tras analizar y discutir los resultados de aplicación del design thinking, se considera que la biblioteca es un lugar propicio para la construcción del conocimiento colectivo, la convivencia y el compartir de ideas, sensaciones, descubrimientos, habilidades y valores, como destacan Juliani et al (2015) y Burguillos (2016).…”
Section: Conclusionesunclassified
See 1 more Smart Citation